RETURN ON INVESTMENT IN EDUCATION IN INDONESIA - Bintang Rizky Abdullah Majo Saibah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the returns to investment in education in Indonesia within the Becker–Mincer human capital framework. Using cross-sectional data from the 2024 Indonesian Labor Force Survey, this research aims to estimate wage premiums associated with different levels of completed education while accounting for work experience, age, gender, employment status, and job location. The analysis employs an extended Mincerian earnings function, where the dependent variable is the logarithm of monthly wages. The results consistently show that education has a positive and statistically significant effect on earnings across all educational levels, with monotonically increasing wage premiums from primary education to postgraduate degrees. Work experience exhibits a positive effect on wages, while its quadratic term is negative, confirming diminishing returns over the life cycle, in line with standard human capital theory predictions. Further disaggregation reveals that although average female wages remain lower than male wages, women experience higher marginal returns to education, particularly at diploma, undergraduate, and postgraduate levels. Additionally, returns to education are higher in urban areas and among salaried employees compared to rural areas and the self-employed. Overall, the findings provide strong empirical evidence that education functions as a productive investment in Indonesia, contributing to income differentials shaped by gender, job characteristics, and labor market structure.